2020
DOI: 10.1002/hbm.25240
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐based cognitive therapy on bereavement grief: Alterations of resting‐state network connectivity associate with changes of anxiety and mindfulness

Abstract: Bereavement, the experience of losing a loved one, is one of the most catastrophic but inevitable events in life. It causes grief and intense depression-like sadness. Recent studies have revealed the effectiveness and proficiency of mindfulness-based cognitive therapy (MBCT) in emotional regulation among bereavement populations. MBCT improves the well-being of the bereaved by enhancing cognitive performances. Regarding the neural correlates of bereavement grief, previous studies focused on the alleviation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 58 publications
4
8
0
Order By: Relevance
“…Our results demonstrated increased theta power in the bilateral frontal lobes, the left temporoparietal region and the right occipital region and enhanced phase synchronizations in the theta band mainly in the right hemisphere after MBCT. These results are consistent with previous suggestions that mindfulness meditation produces increased theta power ( 39 , 40 ), as well as alterations in functional connectivity across brain networks ( 19 , 41 , 42 ). In a pilot study ( 43 ), individuals with bipolar disorder showed decreased theta-band power, and post-MBCT individuals showed an increasing trend in theta power.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrated increased theta power in the bilateral frontal lobes, the left temporoparietal region and the right occipital region and enhanced phase synchronizations in the theta band mainly in the right hemisphere after MBCT. These results are consistent with previous suggestions that mindfulness meditation produces increased theta power ( 39 , 40 ), as well as alterations in functional connectivity across brain networks ( 19 , 41 , 42 ). In a pilot study ( 43 ), individuals with bipolar disorder showed decreased theta-band power, and post-MBCT individuals showed an increasing trend in theta power.…”
Section: Discussionsupporting
confidence: 93%
“…It is accepted that theta band subserves recruitment of metaawareness and cognitive control to sustain the meditative state (17), while alpha band maintains the cortical arousal to avoid perturbations by external stimuli (18). Evidence from functional magnetic resonance imaging (fMRI) studies have suggested that the default mode network (DMN), frontoparietal network (FPN), cingulo-opercular network (CON), and the reorganization of internetworks are also important in mindfulness-based interventions (19)(20)(21)(22). However, the mechanisms by which mindfulness-based neuroplasticity alleviates depression and rumination require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…A potential explanation for this phenomenon was that the MBSR intervention was not effective in some of the participants, and therefore no neurophysiological change was introduced. The same phenomenon was also found in our previous mindfulness study on the bereaved individuals (Feng-Ying Huang et al, 2021) that some of them had their mindfulness levels decreased after the 8-week mindfulness intervention. The phenomenon suggested that mindfulness training did not guarantee success for everyone.…”
Section: Discussionsupporting
confidence: 83%
“…A potential explanation for this phenomenon was that the MBSR intervention was not effective in some of the participants, and therefore, no neurophysiological change was introduced. The same phenomenon was also found in a previous mindfulness study on the bereaved individuals (Huang et al, 2021) that some of them had their mindfulness levels decreased after the 8-week mindfulness intervention. The phenomenon suggested that mindfulness training did not guarantee success for everyone.…”
Section: Intervention Effect Of Mbsrsupporting
confidence: 83%